Influence of Work-Related and Personal Characteristics on the Burnout Risk among Full- and Part-Time Teachers - Seibt, Reingard (Int J Environ Res Public Health, 2021)
Teachers are at increased risk of stress-related illnesses and burnout symptoms. Thus, a cross-sectional study involving 6109 full-time and 5905 part-time teachers at upper-level secondary schools examined the influence of presumed work-related and personal characteristics on burnout risk between January and April 2018. Burnout was recorded using the Maslach Burnout Inventory—General Survey (MBI-GS). Work-related characteristics were weekly working hours and work stress, operationalized with the effort-reward imbalance (ERI) model. Overcommitment and the inability to recover were determined as personal characteristics. Multiple linear regression analyses were performed, adjusted for age and gender. Overall, 47% of the teachers reported burnout symptoms and 3% had an indication of burnout. Full-time and part-time teachers did not differ in their risk of burnout. ERI, overcommitment, and inability to recover were identified as predictors of burnout risk (explained variance: 29%), whereby the inability to recover was the strongest predictor. In contrast, weekly working hours, extent of employment, gender and age were not related to the burnout risk. ERI was found in 33%, inability to recover in 36% and overcommitment in 39% of all the teachers studied. In particular, the inability to recover should be taken into account as an early indicator of burnout.